2016
DOI: 10.1186/s12864-016-2412-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral gene interaction hierarchy analysis of the cell death gene response emphasizes the significance of cell cycle genes following unilateral traumatic brain injury

Abstract: BackgroundDelayed or secondary cell death that is caused by a cascade of cellular and molecular processes initiated by traumatic brain injury (TBI) may be reduced or prevented if an effective neuroprotective strategy is employed. Microarray and subsequent bioinformatic analyses were used to determine which genes, pathways and networks were significantly altered 24 h after unilateral TBI in the rat. Ipsilateral hemi-brain, the corresponding contralateral hemi-brain, and naïve (control) brain tissue were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…The mechanism involved in secondary injury is more complicated [3][4][5]. It includes delayed cell death (such as the newly discovered ferroptosis [6]), brain edema, metabolic defects [7], and blood-brain barrier damage caused by biochemical and physiological changes after trauma [8].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism involved in secondary injury is more complicated [3][4][5]. It includes delayed cell death (such as the newly discovered ferroptosis [6]), brain edema, metabolic defects [7], and blood-brain barrier damage caused by biochemical and physiological changes after trauma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although severe TBI is one of the main causes of death or disability in patients, mild or moderate TBI is a leading cause of long-term disability including seizures and emotional and behavioural issues [2]. The damage to the cranium and the intracranial contents caused by a TBI can be divided into the primary injury and delayed secondary injury, which is more profound and includes axonal shearing [3], neuroinflammation [4,5], neurochemical changes [6,7], brain edema [8], vascular injury [9], cell apoptosis [10] and mitochondrial dysfunction [11].…”
Section: Introductionmentioning
confidence: 99%
“…A plausible reason for this is that whereas preclinical studies are able to examine neuronal gene-activity changes clinical studies are restricted to the used of primarily peripheral blood. An example of this is a recent study in a rat model of TBI which showed that brain tissue-related changes in gene-activity were related to cell death and survival gene pathways ( White et al, 2016 ), as well as inflammation gene-pathways ( Sabir et al, 2015 ). Within preclinical studies, there are both studies using in vitro and in vivo induced TBI models, with a very interesting study that compared both models using a genome-wide approach to have differential gene expression related to genes that direct the function of amyloid precursor protein to the recycling pathway by direct binding and away from amyloid beta producing enzymes, in both TBI models ( Lamprecht et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%